PERBANDINGAN DOSIS TERHADAP VARIASI KEDALAMAN DAN LUAS LAPANGAN PENYINARAN (BENTUK PERSEGI DAN PERSEGI PANJANG) PADA PESAWAT RADIOTERAPI COBALT-60 - Dortua Helena Sidabutar; Evi Setiawati (Youngster Physics Journal, 2014)
A research on the determination of the dose of radiation to the shape of the field square and rectangular fields, this is because the cancer is irregular morphology (irregular). If the radiation dose given is not in accordance with the size, as well as cancer cell geometry is happening is damage healthy tissue surrounding the cells. Determination of the dose is done by adjusting the gantry position Cobalt-60 aircraft at an angle of 0 °, the distance (SSD) radiation source 80 cm from the surface of the phantom which has been coupled with an electrometer and computer devices. For wide field irradiation with a square shape set with field size (6.6 x 6.6), (10.8 x 10.8), (12 x 12), (13.3 x 13.3), and (14 , 2 x 14.2) cm. For a broad field with a rectangular field shape is set by the size (5 x 10), (10 x 12), (10 x 15), (10 x 20) and (10 x 25) cm. Further irradiation for each phantom depth of 1, 3, 5, 7, 9 cm for 60 sekon in a sequence corresponding variations in the size of the specified field as much as 3x (three times) measurements, so that the average value obtained. From the determination and comparison of research results in the field of irradiation dose to the shape of square and rectangular fields, obtained dose values between square and rectangular field is almost the same, is the difference between 0.04 to 1.30 Gy. This result is certainly more convincing in the broad field of use square and rectangular fields in conducting irradiation. This result has also been successfully proven formulation A / C that has been done. Then the value of the dose received phantom decrease with increasing depth phantom is used, with the state of doses already passed the point of his dmax.Keywords: radiotherapy, irradiation field, the depth of phantom